Non-alcoholic steatohepatitis pathogenesis: sublethal hepatocyte injury as a driver of liver inflammation - Ibrahim, Samar H; Hirsova, Petra; Gores, Gregory J (Gut, 2018)
A subset of patients with non-alcoholic fatty liver disease develop an inflammatory condition, termed non-alcoholic steatohepatitis (NASH). NASH is characterised by hepatocellular injury, innate immune cell-mediated inflammation and progressive liver fibrosis. The mechanisms whereby hepatic inflammation occurs in NASH remain incompletely understood, but appear to be linked to the proinflammatory microenvironment created by toxic lipid-induced hepatocyte injury, termed lipotoxicity. In this review, we discuss the signalling pathways induced by sublethal hepatocyte lipid overload that contribute to the pathogenesis of NASH. Furthermore, we will review the role of proinflammatory, proangiogenic and profibrotic hepatocyte-derived extracellular vesicles as disease biomarkers and pathogenic mediators during lipotoxicity. We also review the potential therapeutic strategies to block the feed-forward loop between sublethal hepatocyte injury and liver inflammation.
Keywords: hepatocyty; Non-alcoholic Fatty Liver Disease; inflammation; Hepatitis; Hepatocytes; signální transdukce; hepatitida; Lipids; nonalcoholic steatohepatitis; lipidy; Animals; nealkoholová steatóza jater; lidé; Liver; játra; Humans; zvířata; Signal Transduction